Notes on the genus Mada Mulsant with description of a new Andean species (Coleoptera: Coccinellidae: Epilachnini) - Szawaryn, Karol (Zootaxa, 2015)
Mada andeana, a new species from the Andes is here described. Diagnostic characters are illustrated for both male and female. Mada durantae González et Gómez is here synonymized with Mada inepta (Gorham), new synonymy.